Prešernovo po "Železnoj cesti" hrepenenje - Flaker, Aleksandar (Slavistična revija, 2006)
The article reveals whta the introduction of the railroad (železna cesta, Eisenbahn) brought - in broadest and particularly in metaphorical sense - to European literature or, rather, to literature in general.
Keywords: 19th century; foreing lands; hrepenenje; longing; Prešeren, France; railroad; romantika; Slovene literature; Slovene poetry; slovenska književnost; slovenska poezija; tujina; železnica